Artichoke (Cynara cardunculus L. var. scolymus) waste as a natural source of carbonyl trapping and antiglycative agents. (October 2017) - Maietta, Mariarosa; Colombo, Raffaella; Lavecchia, Roberto; Sorrenti, Milena; Zuorro, Antonio; Papetti, Adele
Abstract: The role of polyphenolic compounds extractable from artichoke solid wastes in the formation of advanced glycation end products (AGEs) was studied. Outer bracts and stems were extracted using different water-ethanol mixtures and HPLC-DAD analyses indicated aqueous and hydro-alcoholic 20:80 stem extracts as the richest in polyphenols. The samples were characterized in their phenolic composition (using mass spectrometry) and antioxidant capacity. Antiglycative capacity was evaluated by in vitro BSA-sugars (glucose, fructose, and ribose) and BSA-methylglyoxal (MGO) tests, formation of Amadori products assay, direct glyoxal (GO) and MGO trapping capacity. Results indicated both extracts as effective inhibitors of fructosamine formation and antiglycative agents. In particular, aqueous extract showed the best activity in the systems containing glucose and fructose, differently from ethanolic extract, that was demonstrated able to better inhibit AGEs formation when ribose or MGO act as precursors. Ethanolic extract was also shown to be able to trap MGO and GO, with efficiency increasing after 24 hours of incubation time. These activities are partially correlated with the antioxidant effect of the extract, as demonstrated by the scavenger capacity against ABTS cation and DPPH stable radicals; this relationship is evident when the model system, containing protein incubated with ribose or MGO, is considered. The different activities of the tested extracts could probably be ascribed to the different composition in chlorogenic acids (CQAs), being aqueous extract richer in 1-CQA, 3-CQA, and 1, 3-di-CQA, and ethanolic extract in 5-CQA, caffeic acid, 1, 5-di-CQA. These findings support further investigations to study the stability of the different CQAs in simil-physiological conditions and the feasibility of artichoke waste as antiglycative agents in food or pharmacological preparations. Chemical compounds: 5-caffeoylquinic acid (PubChem CID 5280633); 3-caffeoylquinic acid (PubChem CID 1794427); 1-caffeoylquinic acid (PubChem CID 10155076); 1, 3-di-caffeoylquinic acid (PubChem CID 24720973); 1, 5 – di-caffeoylquinic acid (PubChem CID 122685); caffeic acid (PubChem CID 689043); apigenin-7-glucuronide (PubChem CID 5319484); methylglyoxal PubChem CID (880); aminoguanidine hydrochloride (PubChem CID 2734687) Graphical abstract: Highlights: Chlorogenic acids from artichoke wastes inhibited protein glycation. Artichoke waste polyphenols directly trapped methylglyoxal. Mono/di-caffeoylquinic acids from artichoke wastes inhibited fructosamine formation. Re-cycling of artichoke by-products is useful in the production of nutraceuticals.